Administering solidarity: Grassroots welfare in post-debt crisis Greece - Henshaw, R (Emerald, 2018)
Purpose – This paper examines what happens as the state relinquishes welfare provision to volunteers. Attending to the ethnographic reality of such practices, to the collection, storage, allocation and distribution of assistance, it explores how the impetus to address poverty is transformed through the process of administering it. Design/methodology/approach – Research was based on one year of ethnographic fieldwork, volunteering in a solidarity organization in Athens. Findings – Administering solidarity, volunteers were confronted with practical, logistic problems. Attempting to resolve these, they resorted to technical, administrative devices. Yet through these efforts, the volunteers systematized not only their activities, but also their view of rights themselves. Solidarity ethics were subtly transformed into values of fairness, efficiency, and impartiality. As a result, the help they offered became impersonal and material, omitting the political dimensions of their work. Originality/value – This paper applies insights from ethnographies of humanitarian organization that emphasize the material, embodied qualities of moral labour. Doing so, it illustrates how seemingly benign practices, such as administration, have fundamentally ethical qualities.